2000
DOI: 10.1046/j.1469-0691.2000.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes and clinical manifestations of group B streptococcal infections in western Sweden

Abstract: Serotype III was the single most frequent GBS isolate from infants and adults. Serotype V, which appeared first in 1992, was the third most frequent isolate. A vaccine containing five GBS capsular polysaccharides appears to be appropriate for the Swedish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
26
4
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 26 publications
9
26
4
4
Order By: Relevance
“…It has been reported that the Ia, II, III, V and X antigens are commonly observed in GBS strains isolated from bovine milk (Finch & Martin, 1984 Duarte et al, 2004), whereas Ia, Ib, Ic, II, III, IV and V antigens are found in GBS from human vaginal specimens (Jelinkova, 1977;Schuctat & Wenger 1994;Berg et al, 2000;Spellerberg, 2000;Ko et al, 2001). In the present study, GBS serotype III and VII were found to be the most frequent serotypes in bovine isolates, but not in human isolates.…”
Section: Serotyping Resultscontrasting
confidence: 46%
See 1 more Smart Citation
“…It has been reported that the Ia, II, III, V and X antigens are commonly observed in GBS strains isolated from bovine milk (Finch & Martin, 1984 Duarte et al, 2004), whereas Ia, Ib, Ic, II, III, IV and V antigens are found in GBS from human vaginal specimens (Jelinkova, 1977;Schuctat & Wenger 1994;Berg et al, 2000;Spellerberg, 2000;Ko et al, 2001). In the present study, GBS serotype III and VII were found to be the most frequent serotypes in bovine isolates, but not in human isolates.…”
Section: Serotyping Resultscontrasting
confidence: 46%
“…In the present study, GBS serotype III and VII were found to be the most frequent serotypes in bovine isolates, but not in human isolates. The importance of the invasive GBS serotype III strains among human isolates is well known (Berg et al, 2000;Ko et al, 2001). GBS serotype III has been incriminated as the major colonizing strain in pregnant women (Finch & Martin, 1984;Berg et al, 2000;Moyo et al, 2002).…”
Section: Serotyping Resultsmentioning
confidence: 99%
“…Novos recursos moleculares para detecção do S. agalactiae diretamente em amostras de sangue estão sendo utilizados, alguns automatizados, que, além de mais sensíveis, rápidos e padronizados, poderão superar algumas destas limitações e serem úteis para fins clínicos e epidemiológicos 23,26 . Quanto à prevalência dos sorotipos Ia, III e V em nosso estudo, condizem com os achados em outros países em amostras reto-vaginais 2,4,7,[27][28][29][30][31][32][33][34][35][36] , sendo exceção o Japão, onde predominam o VI e VIII 37 . Estes sorotipos, por nós encontrados, também estão relacionados à maior virulência e, portanto, associados à maioria das infecções neonatais, maternas e em outras populações [1][2][3][4]9 .…”
Section: Discussionunclassified
“…is one of the most common pathogens causing meningitis, bacteremia, and pneumonia, with high mortality rates in neonates, [1][2][3] non-pregnant women, the elderly, and immuno-compromised patients. [4,5] To treat GBS infection, penicillin, ampicillin, and cefazolin are the drugs of choice; for patients allergic to penicillin or cephalosporins, vancomycin, macrolides (such as erythromycin, azithromycin, and clarithromycin), and lincosamides (clindamycin) may be used as the alternative drugs.…”
Section: S Treptococcus Agalactiae (Group B Streptococcus Gbs)mentioning
confidence: 99%